1999
DOI: 10.1002/hep.510300425
|View full text |Cite
|
Sign up to set email alerts
|

Expression of connective tissue growth factor in experimental rat and human liver fibrosis

Abstract: Connective tissue growth factor (CTGF) stimulates in vitro fibroblast proliferation and extracellular matrix synthesis. The aim of this study was to assess the role of CTGF in liver fibrogenesis. CTGF expression was investigated both at the protein and mRNA level in biopsies of chronic liver diseases, in experimental models of liver fibrosis, and in hepatic stellate cells in culture. CTGF immunostaining was observed in most human liver biopsies with significant fibrosis. An increase of CTGF immunostaining was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
240
2
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(262 citation statements)
references
References 25 publications
12
240
2
7
Order By: Relevance
“…1,8 -10 Furthermore, thrombin-induced activation of PAR 1 stimulates the synthesis and shedding of profibrogenic factors such as heparin-binding epidermal growth factor, PDGF, connective tissue growth factor, fibroblast migration and proliferation, and extracellular matrix production, providing a system that detects tissue injury and triggers a set of cellular responses that contribute to inflammation and tissue repair and remodeling. 6,7,37 Thrombin has been involved in hepatic fibrogenesis in humans, as well in experimental models of liver injury. 5,38 Immunohistochemistry and in situ hybridization studies have demonstrated, that although PAR 1 is expressed in the normal liver in the endothelial lining of the hepatic sinusoids, its expression is up-regulated in response to acute or chronic liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…1,8 -10 Furthermore, thrombin-induced activation of PAR 1 stimulates the synthesis and shedding of profibrogenic factors such as heparin-binding epidermal growth factor, PDGF, connective tissue growth factor, fibroblast migration and proliferation, and extracellular matrix production, providing a system that detects tissue injury and triggers a set of cellular responses that contribute to inflammation and tissue repair and remodeling. 6,7,37 Thrombin has been involved in hepatic fibrogenesis in humans, as well in experimental models of liver injury. 5,38 Immunohistochemistry and in situ hybridization studies have demonstrated, that although PAR 1 is expressed in the normal liver in the endothelial lining of the hepatic sinusoids, its expression is up-regulated in response to acute or chronic liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…CTGF plays a central role in the pathogenesis of hepatic fibrosis by triggering activation and transformation of quiescent hepatic stellate cells into myofibroblasts, and it also stimulates the production of CTGF itself 21, 22. Activated stellate cells over‐produce collagens, fibronectin and laminin under stimulation with CTGF 23.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has suggested that upregulation of CTGF might be a central pathway during HSC activation and hepatic fibrogenesis by mediating many of the profibrotic effects of TGF-␤ (1,41,42,53). CTGF expression in HSCs is significantly enhanced during the process of activation in vitro and in vivo (41,53).…”
mentioning
confidence: 99%
“…CTGF expression in HSCs is significantly enhanced during the process of activation in vitro and in vivo (41,53). HSCs are the major cellular source of CTGF in the liver during liver fibrogenesis (42). In response to exogenous CTGF, HSCs demonstrate increased migration, proliferation, adhesion, and expression of type I collagen (6,41).…”
mentioning
confidence: 99%